[PP.03.11] PREHYPERTENSION IS ASSOCIATED WITH CHRONIC KIDNEY DISEASE IN EUROPEAN RURAL POPULATION- DATA FROM BRISGHELA HEART STUDY (ITALY) AND ENAH STUDY (CROATIA). (September 2016) - Parini, A.; Ivkovic, V.; Vrdoljak, A.; Baric, M. Abramovic; Bacchelli, S.; Cagnati, M.; Cicero, A.F.G.; D'Addato, S.; Esposti, D. degli; Fucek, M.; Grandi, D.; Ivandic, E.; et al.
Abstract : Objective: Chronic kidney disease (CKD) is a silent global epidemic. Hypertension and diabetes are most important risk factors. As prehypertension (PHT) was associated with increased cardiovascular (CV) and renal risk, our aim was to analyze association of PHT with CKD in European rural continental population. Design and method: In this international prospective long-term follow up study data on 5162 subjects (m 2387) from BrEna cohort formed from original cohorts of Brisighella Heart Study (Italy) and ENAH study (Croatia) were analyzed. Them 3389 (m 1456) were eligible for further analyses, and 1335 (m 541) were followed up for average period of 100 months (IQ84–120); 11.337 person years. CKD was defined as eGFR < 60 ml/min (MDRD), HT as BP > = 140/90 mmHg and/or taking antihypertensive drugs, and PHT according to JNC-7 (PHTJ) and ESH stratification (PHTE). At the end of follow-up there were 236 new-onset CKD patients. Results: Prevalence of PHTJ was 25.8% (m vs. w 28.4vs.23.9%;p < 0.05), PHTE 7.8% (m vs.w 8.5vs.7.2; p>0.05). Prevalence of CKD in the whole group was 12.1% (m vs. w. 8.1 vs.15.2; p < 0.01). In the whole group prevalence of CKD increases across BP categories from optimal BP, PHTJ, PHTE and HT (3.2 vs.4.8 vs.5.8 vs.17.8, respectively, p < 0.01), as well in men (0.0 vs.3.3. vs. 2.0 vs.11.7, respectively, p < 0.05) and in women (4.1 vs.6.1 vs.8.9 vs.22.5, respectively, p < 0.01). At baseline, in logistic regression adjusted risk (OR) for CKD was not significant comparing PHT vs. NT, and at the end of follow up PHT was not an independent predictor of new-onset CKD even in obese. In the group of new-onset CKD there was no difference in proportion of PHT at start of follow-up. Conclusions: In European rural population prevalence of CKD increases across BP categories. It is higher in PHT than in NT. PHT was not found to be an independent risk factor for new- onset CKD (3a stage) even in subjects with BMI > 30 kg/m2. Longer period of follow-up, as in HUNT study, is needed this association to become evident. Nevertheless, in PHT, particularly obese, it is prudent to monitor kidney function yearly.